The effects of schooling, family and poverty on children's attainment, potential and confidence—Evidence from Kinondoni, Dar es Salaam, Tanzania. (2017) - Humble, Steve; Dixon, Pauline
Highlights: In general school and teacher factors have a negative affect on children's self confidence and their positive attitude to learning;. Electricity in the home increases the likelihood of scoring higher in all tests;. There is an increased likelihood of girls rather than boys reporting themselves as self confident and positive towards learning;. Teachers believe that a child's ability is inherited from their parents and poor parents are not interested in their child's schooling. Abstract: This paper investigates whether pupil's attainment, attitude and self-confidence are associated with teacher beliefs, experience, school characteristics, background and wealth. Data gathered from 1857 poor children living in Kinondoni, Tanzania included test scores, household data, school and teacher information as well as teacher and peer perceptions. Some results are expected, test scores being significantly and positively correlated, teachers identifying good readers as high ability, and peer and teacher nomination around student ability showing significant levels of concordance. Children from wealthier households are less likely to score higher on tests apart from reading. Teacher experience negatively affects all scores apart from Kiswahili. In general school and teacher factors have a negative affect on children's self confidence and positive attitude to learning.